Where things come back : a novel - Whaley, John Corey (Atheneum Books for Young Readers, 2011)
Seventeen-year-old Cullen's summer in Lily, Arkansas, is marked by his cousin's death by overdose, an alleged spotting of a woodpecker thought to be extinct, failed romances, and his younger brother's sudden disappearance.